2022
DOI: 10.56556/jssms.v1i4.293
|View full text |Cite
|
Sign up to set email alerts
|

An empirical investigation of Tobin’s-Q augmented various Asset Pricing Models: Evidence from Pakistan

Abstract: Despite the strong growing popularity of Asset Pricing Models, it is difficult to estimate which factor contributes significantly in explaining average excess portfolio returns particularly in emerging equity market. Using an extensive sample over Jan-1994-Dec-2020 period, this paper aims to extend the literature by augmenting Tobin-Q adjusted risk premium with various unconditional standard asset pricing models which seeks to postulate the nexus between expected portfolios stock returns and risk-factors using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…The results demonstrate that CAPM failed to forecast expected returns, leading to its discovery as redundant and a mispriced risk-factor, which is consistent with recent studies such as (Hasler, & Martineau, 2022;Azam, 2021;2022c;Lohano & Kashif, 2018;Urooj & Shah, 2016). To infer, the monthly returns based on SEM framework show poor CAPM findings in PSX.…”
Section: Structural Equation Model (Sem) Estimatessupporting
confidence: 90%
See 1 more Smart Citation
“…The results demonstrate that CAPM failed to forecast expected returns, leading to its discovery as redundant and a mispriced risk-factor, which is consistent with recent studies such as (Hasler, & Martineau, 2022;Azam, 2021;2022c;Lohano & Kashif, 2018;Urooj & Shah, 2016). To infer, the monthly returns based on SEM framework show poor CAPM findings in PSX.…”
Section: Structural Equation Model (Sem) Estimatessupporting
confidence: 90%
“…On the other hand, the market risk premium exhibits statistically insignificant relationship with portfolio stock returns except one portfolio SBM6 (-0.0488) which shows significant coefficient. The market-factor show mix results in terms of magnitude, three positive (SBM1, SBM4, SBM5) and three negative (SBM2, SBM3, SBM6) which demonstrates inconsistent with the findings of (Azam, 2022c). For all portfolios, the size-factor produces highly statistically significant findings.…”
Section: Structural Equation Model (Sem) Estimatesmentioning
confidence: 64%
“…Before making a decision, potential investors are provided further information about the PSX investment patterns backed up by real-world data. The future potential studies in the similar discipline may be feasible if they investigate Covid-19 era as suggested by (Azam & Azeem, 2021); augmenting Human-Capital as additional factor with nested APMs as suggested by (Azam, 2022a); using GDP-Growth as macroeconomic additional mediating variable proposed by (Azam & Naveed, 2021); recently used Tobin-q as additional factor augmented with APMs advocated by (Azam, 2022b); using Leverage as added factor for further robustness of results as recommended by (Azam & Ilyas, 2011) in their studies. Moreover, employing developed and datasets from different nations, it is feasible to use macroeconomic variables and a variety of statistical and econometrical approaches for further robustness.…”
Section: Discussionmentioning
confidence: 99%
“…The q-ratio is used to measure the efficiency of a firm's investment decisions, and to measure the relative value of a company's stock. The q-ratio can also be used to compare the relative value of different companies in the same industry (Tobin-q, 1969;Azam, 2022c).…”
Section: Tobin-q (Umo)mentioning
confidence: 99%